‫أثر‬‫إدارة‬ ‫المعرفة‬ ‫على‬ ‫تفعيل‬ ‫التسويق‬ ‫الداخلي‬ ‫في‬ ‫الشركة‬ ‫الوطنية‬ ‫للتأمينات‬ ‫‬‫‪‬‬ ‫وكالة‬ ‫عنابة - زين‬ ‫الدين‬ ‫عمارة‬‫; ‬‫عبد‬ ‫الرحمن ‫غالي ‬ (My University, 2017)
Our research focuses on the impact of knowledge management on marketing internally in the company, it is one of the vital marketing management subjects and contemporaries, at this level, it should be mentioned that the primary interest of marketing internal in organizations is the improvement of the capacities and skills of the staff, in order to assume their responsibility and provide quality services to customers. This research also gave a comprehensive and well-detailed view of the theory of knowledge management and its dimensions, as well as the dimensions of internal marketing. The practical study focused on the SAA Annaba insurance sector where we used to establish a questionnaire as a key tool to be able to collect data with people working at this agency, in general the study was mainly focused on the influence of knowledge management on internal marketing at the appropriate agency level.